On Rearing an Ugly Head: Joel-Peter Witkin and the Mysticism of the “Ugly Aesthetic” - Ballen, Amanda (Department of English Language and Literature, 2021)
The contemporary photographer, Joel-Peter Witkin, has described his remaking of some of the most iconic paintings in the history of art as a “divine revolt”. However, there are no attempts to unravel the meaning of this project nor to analyse the visual changes that Witkin has made. This thesis argues that Witkin's re-creations serve to subvert the negation or diminishment of ugliness in art history's depictions of the mystical, and to present the experience of ugliness as alternatively inherently Godly. Through engaging in the problems in philosophical aesthetics, it contrasts the notions “aesthetically ugly” (a quality that cannot be objectively identified and studied because it ascribes aesthetic non-worth) with the “ugly aesthetic”, which refers to the “perceptive-felt” experience of an object. By integrating descriptions of this experience of the ugly aesthetic with those of the early development stage of the “psychoanalytic pre-symbolic”, it provides heuristics with which to identify perceptual identifiers ugly objects, ugly worlds and the expression of ugly feelings in mystical invocations of paintings of three chosen art historical periods and Witkin's recreations. In his reconstructing of the heavenly realms given Renaissance paintings of Leda and the Swan (1510-1515) and The Birth of Venus (1485), Witkin makes a “pre-symbolic” space with ugly objects to present a contrary vision of an ugly dwelling place for God. In amending the Catholic Baroque's Little Fur (1638) and the Protestant Baroque's Still Life of Game, Fish, Fruit and Kitchen Utensils (1646), the artist replaces mystical feelings that imbue scenes of ugly objects with an expression of ugly feelings themselves, thereby guiding the viewer into a full immersion into these objects the real site of Godly experience instead. This theoretical formulation and its application to the works at hand, evidence that Witkin's work points to the mystical power of the ugly aesthetic to unleash a personal and collective memory of Godly reality as ontologically formless and mysterious, and thereby makes a case for ugliness' value.